(untitled) (Portuguese Journal of Family Medicine and General Practice, 2011)
Hon. Mr Director of the Portuguese Journal of General Practice, In publication September / October 2010 RPCG, volume 26, No 5 was published an article entitled "Preventive Activity and Indicators - How Long Sobra" Where there is a claim that is not true.